The Effect of Service Quality on Visitor Satisfaction - Rezky Ratnasari Taufan A (Golden Ratio of Data in Summary, 2023)
This study aims to analyze the impact of service quality on customer satisfaction at Sabar Restaurant in Soppeng Regency, Indonesia. With the increasing competition in the culinary sector, service quality has become a key factor in attracting and retaining customers. This research uses a quantitative approach with a descriptive method, where primary data was obtained through questionnaires and interviews with 99 visitors to Sabar Restaurant, selected through accidental sampling from a total of 18,000 visitors over the past six months in 2023. The variables studied include physical evidence, reliability, responsiveness, assurance, and empathy, and their impact on customer satisfaction. Multiple linear regression analysis was used to test the relationship between these variables. The results show that physical evidence, reliability, and responsiveness do not significantly affect customer satisfaction, although they are expected as standard service features. However, empathy has a positive and significant influence, highlighting the importance of a good relationship between the company and its customers in creating satisfaction. These findings suggest that restaurant managers should focus more on empathy in their services to enhance customer satisfaction and loyalty.